Perceptions of The Use of E-Learning in The English Teaching Activities by Students - Septa Aryanika (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This research aims to explore students’ perceptions of the use of e-learning in English teaching activities. The study was conducted to understand how students respond to and engage with digital learning platforms during their English classes, especially in the context of increasing reliance on online education. Using a qualitative approach, data were collected through questionnaires from college students. The findings reveal that most students perceive e-learning as a helpful tool that offers flexibility, access to various resources, and opportunities for independent learning. However, challenges such as lack of motivation, technical issues, and limited interaction with teachers were also identified. Overall, while students acknowledged the benefits of e-learning in enhancing their English skills, they also emphasized the importance of combining it with traditional face-to-face instruction for more effective learning outcomes. This study highlights the importance of improving digital infrastructure and instructional design to ensure that e-learning is both effective and engaging in English education